Sediment microbiomes associated with critical habitat of the Juvenile American Horseshoe Crab; Limulus polyphemus - J. Petersen; C.P. Colon; J.L. Joyner (Global Journal of Environmental Science and Management)
Plumb Beach, Brooklyn, New York in USA is an important horseshoe crab breeding and nursery ground that has experienced substantial anthropogenic influence, including pollution, erosion and subsequent restoration. Since little is known about the relationship between sediment microbial communities and juvenile horseshoe crab survival, next generation sequencing was used to characterize and compare the sediment microbiome of three distinct areas of Plumb Beach:- a tidal creek with abundant juveniles, East Beach with moderate number of juveniles, and West Beach- a highly disturbed area where juvenile crabs are rarely seen. The microbiome of juvenile crab intestinal content (both dissected gut content and fecal flush content) from the tidal creek site was also examined. The results showed that in our 2017 survey, the overall dominant sediment orders at all beach sites were Vibrionales (30%), Flavobacteriales (22%) and Alteromonadales (21%). Although alpha diversity was similar among the three beach sites, Bray-Curtis distances assessed by Permanova revealed significant differences in Beta diversity, with a unique microbial assemblage found in the tidal creek. Both crab gut and fecal flush samples did not sequence well, showing low species diversity and very high variability. This study is the first to use next generation sequencing to characterize Plumb Beach sediment microbes and the first attempt to examine the gut microbiome of juvenile horseshoe crabs. This information will contribute to understanding the relationships between sediment microbial assemblages and juvenile crab populations within this important urban habitat.